English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

letthe intger be x
(2x)^2=6+10x
4x^2-10x+6=0
4x^2-6x-4x+6=0
2x(2x-3)-2(2x-3)=0
(x-3)(2x-3)=0
x=3

2006-12-10 06:06:36 · answer #1 · answered by raj 7 · 0 0

(2x)^2= 10x-6

simplify this expression and get x on one side
4x^2= 10x-6
10x= 4x^2 +6
divide by 2
5x= 2x^2 +3
5= 2x+3/x
x=1

2006-12-10 14:05:59 · answer #2 · answered by travis R 4 · 0 0

fedest.com, questions and answers